Adsorption Characteristics of Anionic Surfactant Sodium Dodecylbenzene Sulfonate on the Surface of Montmorillonite Minerals - Ni, Xiaoming; Li, Zhiheng; Wang, Yanbin (Frontiers in Chemistry, 2018)
The adsorption characteristics of sodium dodecylbenzene sulphonate (SDBS) on the surface of montmorillonite can lay a foundation for obtaining the optimum concentration of the anion surface active agent. The best absorption wavelength of SDBS was determined by ultraviolet spectrophotometer. The standard curve of concentration and absorbance of SDBS were established. The amount of SDBS adsorbed on the surface of montmorillonite at different concentrations was calculated by stirring adsorption method. Scanning electron microscopy-energy dispersive X-ray spectrometry (SEM-EDS), X-ray Diffraction (XRD), Zeta potentiometer, and Fourier transform infrared (FTIR) spectroscopy were used to observe the changes of the structure, main ions, interlayer spacing, potential, and main functional groups on the montmorillonite surface before, and after, adsorption. Scanning electron microscopy, with energy spectrometer (SEM-EDS) test results, showed that the surface of the montmorillonite was rougher after SDBS adsorption, and the adsorption capacity of the surface increased as the SDBS concentration increased. XRD results indicated that SDBS adsorbed on the interlayer of montmorillonite repulsed interlayer water and reduced the interlayer water content. With the increase of SDBS concentration, the interlayer spacing of the montmorillonite available for adsorbing SDBS decreased further. Additionally, interlayer adsorption and surface adsorption exist simultaneously in montmorillonite in SDBS solution. The distribution of total adsorption capacity of SDBS in the layers and on the surface of montmorillonite accords with the adsorption result simulated by a pseudo-second-order kinetic model. The increase in concentration of SDBS adsorbed by montmorillonite is the main reason for the decreased initial adsorption rate. The Zeta potential test showed that the addition of H+ to the SDBS solution could reduce electrostatic repulsion and promote the adsorption of SDBS on montmorillonite. The results of this study provide an experimental basis for the study of the mechanism of SDBS adsorption on montmorillonite.